Preparative Fractionation of Bacterial Proteins from Complex Probiotic Cell Matrices by Continuous Divergent Flow Electrophoresis for Further Downstream Processing - Stastna, Miroslava (Probiotics and antimicrobial proteins, 2025)
Bacterial proteins play important roles in many biological processes. However, many of them remain poorly characterized and their functions not well identified, due to, for example, their low abundances. Preparative fractionation can process and simplify complex biological samples and fractionate them into distinct fractions containing the proteins that are pre-purified from other proteins and unwanted sample impurities. If the proteins in the sample are present in low abundances, continuous collection of fractions allows obtaining sufficient amounts to process them further. Here, the supernatant with bacterial proteins extracted from nine species of probiotic bacterial cells was subjected to preparative fractionation in continuous divergent flow instrumentation working on the basis of bidirectional isotachophoresis/moving boundary electrophoresis. The analysis of the supernatant and collected fractions by SDS-PAGE and gel IEF revealed that the bacterial proteins in the supernatant covered molecular weights from 9 to 160 kDa and isoelectric points from 3.9 to 5.7. The majority of proteins were detected in four neighboring fractions. The analysis of fractions showed that during preparative bidirectional isotachophoresis, the proteins could be uniquely electro-focused and found in a single fraction, enriched as compared to the supernatant and/or separated from the proteins in other fractions. The proteins in separated pre-purified fractions are suitable for further analyses and procedures.
Keywords: Bacterial proteins; Probiotic cells; Continuous divergent flow electrophoresis; Preparative fractionation